Impact of Substituent Variation on the Presence of Thermal Spin Crossover in a Series of Mononuclear Iron(III) Schiff Base Complexes with Terminal Pseudohalido Co‐ligands. Issue 20 (28th December 2017) - Pogány, Lukáš; Brachňaková, Barbora; Moncol, Ján; Pavlik, Ján; Nemec, Ivan; Trávníček, Zdeněk; Mazúr, Milan; Bučinský, Lukáš; Suchánek, Lubomír; Šalitroš, Ivan
Abstract: A series of novel iron(III) complexes of the general formula [Fe(L)X] (where L is a dianion of pentadentate Schiff base ligand N, N ′‐bis(2‐hydroxy‐3, 5‐dimethylphenylphenyl)methylidene‐1, 6‐diamino‐3‐azapentane=H2 L1 for1 and2 ; N, N ′‐bis(2‐hydroxy‐3‐ethoxyphenylmethylidene)‐1, 6‐diamino‐3‐azapentane=H2 L2 for3 and3⋅C3 H6 O ) and X is terminal pseudohalido ligand (X=N3 for1, X=NCS for2, and X=NCSe for3 and3⋅C3 H6 O ) were synthesized and thoroughly characterized. Magnetic measurements revealed the above room temperature spin crossover for isomorphic complexes1 and2 ( T 1/2 =441 K and T 1/2 =435 K, respectively), whereas the solvent‐free complex3 showed a half complete spin crossover ( T 1/2 =250 K), which was detected by variable temperature crystallography as well. On the other hand, solvated complex3⋅C3 H6 O exhibited permanent high spin state behaviour and either recrystallization or in situ thermal desolvation converts3⋅C3 H6 O to solvent‐free and spin‐crossover‐active form3 . Magnetic properties of all the reported complexes were also supported by EPR spectroscopy experiments and in addition, DFT and ab initio calculations were employed for the evaluation of the g ‐factor and zero field splitting parameters. Abstract : Spin and flip : Parallel variation of Schiff‐base ligand substituents and terminal pseudohalido ligand anions allowed for the tuning of spin crossover characteristics in a series of mononuclear iron(III) complexes. The spin‐crossover event was monitored using various experimental techniques, and the results were supported by theoretical calculations.